DEVELOPING INTERACTIVE MEDIA IN LEARNING MATHEMATICS BY USING MACROMEDIA FLASH 8 ON MATERIAL TWO VARIABLES LINEAR EQUATION SYSTEM OF CLASS X SMK - Guntur Prabowo; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Rapid technological developments, make innovation development of instructional media of mathematics as a tool for learning. Media developed learning because students are still challenging to understand the material system of linear equations, so that the need for renewable innovations in mathematics for students in learning to overcome boredom. The use of laboratory and LCD (Liquid Crystal Display) is still not widely used in learning mathematics. This study aims to develop teaching media in the form of interactive media using Macromedia Flash 8 in the learning of mathematics in SMK on the material of the Two-Variable Linear Equations System and test the feasibility. This study focused on developing mathematics learning media packaged in a Compact Disc (CD). The development of research using (Research and Development). The subject of research is matter experts, media experts, and National Vocational High School Berbah (SMK Nasional Berbah) and Muhammadiyah Vocational High School 3 Yogyakarta (SMK Muhammadiyah 3 Yogyakarta). Learning media is validated by three votes materials experts, three expert media, and the subject of the trial of 10 students on a test smaller classes. All students in the pilot class of high use assessment instruments or sheets instrument quality research materials and instructional media student response. Data analysis techniques use qualitative analysis that is converted into quantitative value. Data collection techniques in the form of interviews, questionnaires, and observations. This research has succeeded in developing a medium of mathematics learning that has quality on every aspect of assessment with an average score of 76,67 material experts with good criteria and an average score of expert media assessment 40,33 with Very Good criteria. While the score of student response 69,74 with the score on the small class test and big class test with good criterion. Based on these assessments, this math learning media is worthy of being used as a learning resource for students.